AN INVESTIGATION OF THE EFFECTS OF WIND VELOCITY ON THE PERFORMANCE OF TURBINES AND GENERATORS - Lestari, Kiki Rezki; Alviana, Izkia Dwi; Gunadi, Sunartoto; Wati, Erna Kusuma; Santoso, Hari Hadi (PT. Hafasy Dwi Nawasena, 2024)
Variations in wind speed at 4,6 and 8 m altitudes were analyzed using a 24-hour dataset. The greatest recorded wind velocity was 3.3 m/s at a height of 8 meters, and the lowest was around 2.4 m/s at a height of 4 meters. The investigation also identified discrepancies in velocity between the generator and turbine while they were operating with and without a load. The turbine's speed increased when there was no weight present. The peak wind velocity reached 3.9 meters per second, accompanied by a similar variation of 5.4 rotations per minute. The average discrepancy in rotational velocity between the turbine and generator during periods of low wind was 3.74 RPM. This discovery establishes a fundamental basis for comprehending the movement of wind and enabling future in-depth explorations in the field of atmospheric sciences. The generator's performance is assessed by the measurement of current and voltage, which serves to highlight its versatility and effectiveness. The correlation between wind velocity and generator rotational speed is crucial for energy conversion, since the turbine's velocity needs to be adjusted to match the heightened load, affecting the generator's speed.